Carbon dioxide-based resin coating and preparation method thereof
By using polycarbonate resins made of copolymerization of carbon dioxide, epoxy compounds and acid anhydrides, combined with modified materials and other additives, a recyclable and degradable carbon dioxide-based resin coating was prepared, which solved the shortcomings of existing polyethylene coatings in terms of environmental degradation and sustainability, and achieved high-performance and environmentally friendly coating applications.
Patent Information
- Application Number
- CN202411959056.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-02-28
AI Technical Summary
Existing polyethylene coatings have shortcomings in environmentally friendly degradation and sustainability, making it difficult to meet the demand for recyclable and degradable materials.
A polycarbonate resin composed of copolymerized carbon dioxide, epoxy compounds and acid anhydrides is used as the main material, and combined with modification materials, leveling agents, anti-aging agents and dry powder flow additives, a single-component carbon dioxide-based resin coating that can be directly used was prepared.
This coating not only has excellent waterproofness, UV resistance and corrosion resistance, but also can force biodegradation after reaching its service life, reducing greenhouse gas emissions, and promoting the sustainable development of the plastics industry.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating materials, and in particular relates to a carbon dioxide-based resin coating and a preparation method thereof. Background Art
[0002] In the field of resin coating technology, polyethylene coatings are favored for their environmental protection, safety and corrosion resistance. For example, patent CN112480752A discloses a polyethylene powder coating with high oil resistance and adhesion, and its raw materials include: polyethylene resin, bisphenol A type epoxy resin, terminal carboxyl saturated polyester resin, maleic anhydride grafted modified polyethylene, curing agent, leveling agent, antioxidant and dry powder flow aid. The coating has high adhesion to the surface of the steel pipe, good oil resistance, strong water penetration resistance, and good leveling of the coating appearance. In addition, patent CN114957917B discloses a petrochemical anti-corrosion and anti-creep coating, which can also show strong bonding and high toughness in applications on metal substrate surfaces. However, these coatings are all traditional polyethylene coatings, and they still need to be improved in terms of environmental degradation and sustainability. Summary of the invention
[0003] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a recyclable and degradable carbon dioxide-based resin coating and a preparation method thereof.
[0004] The technical solution adopted by the present invention to solve the technical problem is: a carbon dioxide-based resin coating, which is composed of 10 to 90 parts by weight of polycarbonate resin and 10 to 85 parts of auxiliary agent. The molecular chain of the polycarbonate resin contains random or block-structured polycarbonate segments, polyester segments and arbitrary polyether segments.
[0005] The present invention is a single-component coating that can be used directly without mixing components A and B when used like polyurethane coatings. The coating uses polycarbonate resin as the main raw material and has better waterproofness, UV resistance and corrosion resistance than traditional coatings using PE as the main raw material.
[0006] Preferably, the weight portion of the polycarbonate resin is 30-90 parts, and the weight portion of the additives comprises 10-70 parts of a modifying material, 1-5 parts of a leveling agent, 1-5 parts of an antioxidant, 1-5 parts of a dry powder flow aid, 0-5 parts of a color paste, and 0-100 parts of a solvent.
[0007] The carbon dioxide-based resin coating uses carbon dioxide as a raw material, which helps to reduce greenhouse gas emissions. The main material of the coating, polycarbonate resin, is copolymerized by epoxy compounds, carbon dioxide and anhydride, which not only provides excellent transparency, adhesion and physical properties, but also can be forced to biodegrade after reaching the service life. The added leveling agent and dry powder flow aid improve the construction performance of the coating and make the coating more uniform. The addition of an antioxidant can improve the aging resistance of the coating and extend the service life of the coating. Harmful organic volatiles and heavy metal salts are not added to the coating, ensuring the green safety of the product, which is harmless to human health and the environment. More preferably, the weight parts of the carbon dioxide-based resin coating are composed of: 50-90 parts of polycarbonate resin, 10-20 parts of modified materials, 1-5 parts of leveling agents, 1-5 parts of antioxidants and 1-5 parts of dry powder flow aids, and 0-100 parts of solvents.
[0008] The invention determines whether to add a solvent according to different use methods. The coating can be used directly as a solid coating or can be used as a solution coating after being dissolved in a solvent.
[0009] Preferably, the comonomer of the polycarbonate resin includes an epoxy compound, carbon dioxide and any dibasic acid anhydride, and the molar ratio of the epoxy compound, carbon dioxide and dibasic acid anhydride in the comonomer of the polycarbonate resin is 50-80:100:30-60, and the dibasic acid anhydride is preferably phthalic anhydride or 1,8-naphthalene anhydride. By controlling the molar ratio of the comonomer, a polycarbonate resin with a specific molecular chain structure is obtained, the purpose of which is to improve the tensile strength and elongation at break of the coating, improve the processing fluidity of the copolymer, and make it conducive to the construction and molding of the coating.
[0010] Specifically, the epoxy compound is a combination of one or more C1-C22 alkylene oxides or epoxy ethers.
[0011] Preferably, the epoxy compound is a combination of one or more of ethylene oxide, propylene oxide, cyclohexene oxide, butyl glycidyl ether (BGE), C12-14 alkyl glycidyl ether (AGE) and limonene epoxide.
[0012] More preferably, the epoxy compound is a mixture of cyclohexene oxide and limonene epoxide in a molar ratio of 10:1 to 4. The polycarbonate resin obtained by this combination is used as the main component of the coating, which not only enhances the mechanical properties and chemical stability of the coating, but also improves the renewability and environmental protection of the material by increasing the bio-based components. The double bonds in limonene epoxide provide additional flexibility for the synthesis and post-modification of the material, broadening the application range of the coating, especially in the field requiring high glass transition temperature and transparency.
[0013] When polycarbonate resin made of preferred epoxy compounds is used as the main material of the coating, the obtained coating not only has strong water-blocking, oxygen-blocking and UV-blocking functions, but also has a longer service life under exposure and can be forced to biodegrade after reaching the service life.
[0014] Preferably, in the above carbon dioxide-based resin coating, the modified material is a combination of one or more of polyamide resin, polyvinyl alcohol tert-butyral and phenolic resin. Polyamide resin can improve the brittleness of the coating and improve the bonding ability; polyvinyl alcohol tert-butyral can better improve the impact resistance of the coating. Phenolic resin can improve the toughness and adhesion of the coating.
[0015] More preferably, in the above carbon dioxide-based resin coating, the modified material is polyisobutylene, TPU, EVA, or tert-butylphenol-formaldehyde resin. Tert-butylphenol-formaldehyde resin is formed by the reaction of tert-butylphenol and formaldehyde. This modified phenol-formaldehyde resin enhances the toughness and adhesion of the coating, improves heat resistance and flame retardancy, and improves chemical stability and dimensional stability.
[0016] Preferably, in the above carbon dioxide-based resin coating, the antioxidant is N,N'-diphenylethylenediamine, N,N'-diphenylpropylenediamine or N,N-di(β-naphthyl)-p-phenylenediamine. The preferred antioxidant can absorb ultraviolet rays to prevent polycarbonate from photo-oxidative aging due to ultraviolet irradiation, and can also prevent the ester group of polycarbonate from oxidation, reduce the breakage of end groups and side groups caused by thermal oxidative aging, thereby maintaining the mechanical properties of the coating.
[0017] Preferably, in the above-mentioned carbon dioxide-based resin coating, the leveling agent is carboxylic acrylic resin or epoxy acrylate resin. The preferred leveling agent can better reduce the surface tension of the polycarbonate material, promote the flow of the coating during the coating process, and reduce brush marks and orange peel phenomena. Available models of carboxylic acrylic resin include SC8007, SC8008, and SC8020 of Zhejiang Shuangcai New Materials Co., Ltd., and available models of epoxy acrylic resin include SC300.
[0018] Preferably, in the above-mentioned carbon dioxide-based resin coating, the dry powder flow aid is hydrophobic fumed silica, organic modified bentonite or castor oil derivatives. More preferably, the dry powder flow aid is hydrophobic fumed silica. As a dry powder flow aid, hydrophobic fumed silica can significantly improve multiple properties of carbon dioxide-based resin coatings, including anti-settling, thixotropy, storage stability, salt spray resistance and corrosion resistance, as well as the fluidity and anti-caking properties of powder coatings.
[0019] A method for preparing the above-mentioned carbon dioxide-based resin coating, the preparation steps comprising:
[0020] 1) The polycarbonate resin, the modified material, the leveling agent and the antioxidant are uniformly mixed to obtain a mixed material; the mixed material is extruded and granulated to obtain blend particles;
[0021] 2) Mix the blend particles and dry powder flow aid evenly and grind them into powder.
[0022] The coating prepared by uniform mixing, granulation and grinding of materials has excellent mechanical properties, chemical resistance, weather resistance and environmental protection.
[0023] Preferably, in step 1) of the above preparation method, the extrusion granulation adopts a twin-screw extruder; the aspect ratio of the twin-screw extruder is 35-45:1. The extrusion temperature of the extrusion granulation is 110°C-120°C. This temperature range can ensure the effective processing of the material and avoid the loss of material properties. The extrusion speed is 400r / min-800r / min.
[0024] Preferably, in step 2) of the above preparation method, grinding is performed using a normal temperature disc grinder with a mesh size controlled to be 20-80 meshes.
[0025] Compared with the prior art, the present invention has the following beneficial effects: the present invention proposes an innovative resin coating, which uses polycarbonate copolymerized from carbon dioxide, epoxy compounds and acid anhydride as the main material. This new coating not only has excellent adhesion and mechanical properties, but also uses carbon dioxide as a raw material, reduces greenhouse gas emissions, and promotes the sustainable development of the plastics industry. DETAILED DESCRIPTION
[0026] The present invention is described in detail below by way of examples. Unless otherwise specified, all raw materials used are commercially available, and for the sake of comparison, only solid powder coatings are used as examples in the examples, and in actual use, solvents may be added as needed to form coating solutions.
[0027] Example 1
[0028] 1) Prepare 70 parts of polycarbonate resin, 15 parts of p-tert-butylphenolic resin, 3 parts of N,N'-diphenylethylenediamine, 3 parts of carboxyl acrylic resin and 3 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by epoxy compound, carbon dioxide and phthalic anhydride in a molar ratio of 65:100:45, and the epoxy compound is a mixture of cyclohexene oxide and limonene epoxide in a molar ratio of 10:2.
[0029] The polycarbonate resin, tert-butylphenolic resin, N,N'-diphenylethylenediamine and carboxyl acrylic resin are uniformly mixed to obtain a mixture; the mixture is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 115°C, and the extrusion speed is 500r / min.
[0030] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature disc mill with the mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0031] Example 2
[0032] 1) Prepare 70 parts of polycarbonate resin, 15 parts of polyvinyl alcohol tert-butyral, 3 parts of N,N'-diphenylethylenediamine, 3 parts of carboxyl acrylic resin and 3 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by epoxy compound, carbon dioxide and phthalic anhydride in a molar ratio of 65:100:45, and the epoxy compound is a mixture of cyclohexene oxide and limonene epoxide in a molar ratio of 10:2.
[0033] The polycarbonate resin, polyvinyl alcohol tert-butyral, N,N'-diphenylethylenediamine and carboxyl acrylic resin are uniformly mixed to obtain a mixture; the mixture is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 115°C, and the extrusion speed is 500r / min.
[0034] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature disc mill with the mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0035] Example 3
[0036] 1) Prepare 70 parts of polycarbonate resin, 15 parts of p-tert-butylphenolic resin, 3 parts of N,N'-diphenylethylenediamine, 3 parts of carboxyl acrylic resin and 3 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by cyclohexene oxide, carbon dioxide and phthalic anhydride in a molar ratio of 65:100:45.
[0037] The polycarbonate resin, tert-butylphenolic resin, N,N'-diphenylethylenediamine and carboxyl acrylic resin are uniformly mixed to obtain a mixture; the mixture is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 115°C, and the extrusion speed is 500r / min.
[0038] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature disc mill with the mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0039] Example 4
[0040] 1) Prepare 70 parts of polycarbonate resin, 15 parts of p-tert-butylphenolic resin, 3 parts of N,N'-diphenylethylenediamine, 3 parts of carboxyl acrylic resin and 3 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by BGE, carbon dioxide and phthalic anhydride in a molar ratio of 65:100:45.
[0041] The polycarbonate resin, tert-butylphenolic resin, N,N'-diphenylethylenediamine and carboxyl acrylic resin are uniformly mixed to obtain a mixture; the mixture is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 115°C, and the extrusion speed is 500r / min.
[0042] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature grinding disc mill with a mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0043] Example 5
[0044] 1) Prepare 65 parts of polycarbonate resin, 17 parts of p-tert-butylphenolic resin, 3 parts of N,N-di(β-naphthyl)-p-phenylenediamine, 2 parts of epoxy acrylate resin and 2.5 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by epoxy compound, carbon dioxide and 1,8-naphthalene anhydride in a molar ratio of 50:100:60, and the epoxy compound is a mixture of cyclohexene oxide and limonene epoxide in a molar ratio of 10:1.
[0045] The polycarbonate resin, the modified material, the leveling agent and the antioxidant are uniformly mixed to obtain a mixed material; the mixed material is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 120° C., and the extrusion speed is 400 r / min.
[0046] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature grinding disc mill with a mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0047] Example 6
[0048] 1) Prepare 80 parts of polycarbonate resin, 12 parts of polyamide resin, 2 parts of N,N-di(β-naphthyl)-p-phenylenediamine, 4 parts of epoxy acrylate resin and 3 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by epoxy compound, carbon dioxide and 1,8-naphthalene anhydride in a molar ratio of 80:100:30, and the epoxy compound is a mixture of cyclohexene oxide and limonene epoxide in a molar ratio of 10:4.
[0049] The polycarbonate resin, the modified material, the leveling agent and the antioxidant are uniformly mixed to obtain a mixed material; the mixed material is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 110° C., and the extrusion speed is 800 r / min.
[0050] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature grinding disc mill with a mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0051] Example 7
[0052] 1) Prepare 50 parts of polycarbonate resin, 20 parts of polyvinyl alcohol tert-butyral, 5 parts of N,N'-diphenylpropylenediamine, 5 parts of carboxyl acrylic resin and 5 parts of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by epoxy compound, carbon dioxide and phthalic anhydride in a molar ratio of 50:100:60, and the epoxy compound is a mixture of ethylene oxide and propylene oxide in a molar ratio of 10:3.
[0053] The polycarbonate resin, the modified material, the leveling agent and the antioxidant are uniformly mixed to obtain a mixed material; the mixed material is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 110° C., and the extrusion speed is 800 r / min.
[0054] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature disc mill with the mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0055] Example 8
[0056] 1) Prepare 90 parts of polycarbonate resin, 10 parts of p-tert-butylphenolic resin, 1 part of N,N'-diphenylethylenediamine, 1 part of epoxy acrylate resin and 1 part of hydrophobic fumed silica by weight, wherein the polycarbonate resin is copolymerized by epoxy compound, carbon dioxide and phthalic anhydride in a molar ratio of 80:100:30, and the epoxy compound is a mixture of ethylene oxide and cyclohexene oxide in a molar ratio of 10:3.
[0057] The polycarbonate resin, the modified material, the leveling agent and the antioxidant are uniformly mixed to obtain a mixed material; the mixed material is extruded and granulated by a twin-screw extruder to obtain blend particles, the extrusion temperature is 120° C., and the extrusion speed is 400 r / min.
[0058] 2) The blend particles and the hydrophobic fumed silica are uniformly mixed and then ground using a normal temperature disc mill with the mesh number controlled to be 60 meshes to obtain a carbon dioxide-based resin coating.
[0059] The coatings prepared in the above examples were subjected to performance tests such as tensile strength and elongation at break.
[0060] Sample preparation: Take the coating powder of each example and put it into a mold sprayed with a release agent, place it on a flat vulcanizer and preheat it at 180°C for 10 minutes, then pressurize it to 5MPa, exhaust it three times and keep the pressure for 5 minutes, and then cool it to room temperature at a rate of 15°C per minute. Test according to standard GB / T1040, the test results are shown in Table 1.
[0061] Transparency: The transparency of the coating is determined by measuring the transmittance in accordance with GB / T 1721-2008.
[0062] Adhesion test: Take a 159×6×2000mm steel pipe with anti-rust grease sprayed on the surface. After the surface of the steel pipe is treated by shot blasting, the steel pipe is preheated to 200°C. After preheating, the coating powder of each embodiment is coated with a coating thickness of 900μm~950μm. After natural cooling and leveling, the coating adhesion test is carried out according to the test method of traditional polyethylene coatings in standard CJ / T120. The test results are shown in Table 1.
[0063] Table 1 Performance test results
[0064] .
[0065] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A carbon dioxide-based resin coating, characterized in that: The composition by weight is: 10-90 parts of polycarbonate resin and 10-85 parts of auxiliary agent. The molecular chain of the polycarbonate resin contains polycarbonate segments, polyester segments and arbitrary polyether segments of random or block structure.
2. A carbon dioxide-based resin coating according to claim 1, characterized in that: The weight portion of the polycarbonate resin is 30-90 parts, and the weight portion of the auxiliary agent comprises 10-70 parts of a modified material, 1-5 parts of a leveling agent, 1-5 parts of an antioxidant, 1-5 parts of a dry powder flow aid, 0-5 parts of a color paste, and 0-100 parts of a solvent.
3. A carbon dioxide-based resin coating according to claim 1 or 2, characterized in that: The comonomers of the polycarbonate resin include epoxy compounds, carbon dioxide and any dibasic acid anhydride; the molar ratio of the epoxy compounds, carbon dioxide and dibasic acid anhydride is 50-80:100:30-60.
4. A carbon dioxide-based resin coating according to claim 3, characterized in that: The epoxy compound is a combination of one or more C1-C22 alkylene oxides or epoxy ethers.
5. A carbon dioxide-based resin coating according to claim 2, characterized in that: The modified material is a combination of one or more of polyisobutylene, TPU, EVA, polyamide resin, polyvinyl alcohol tert-butyral and phenolic resin.
6. A carbon dioxide-based resin coating according to claim 2, characterized in that: The antioxidant is N,N'-diphenylethylenediamine, N,N'-diphenylpropylenediamine or N,N-di(β-naphthyl)-p-phenylenediamine.
7. A carbon dioxide-based resin coating according to claim 2, characterized in that: The leveling agent is carboxyl acrylic resin or epoxy acrylate resin.
8. The carbon dioxide-based resin coating according to claim 2, characterized in that: The dry powder flow aid is hydrophobic fumed silica.
9. A method for preparing the carbon dioxide-based resin coating according to any one of claims 1 to 8, characterized in that: The preparation steps include: 1) The polycarbonate resin, the modified material, the leveling agent and the antioxidant are uniformly mixed to obtain a mixed material; the mixed material is extruded and granulated to obtain blend particles; 2) Mix the blend particles and dry powder flow aid evenly and grind them into powder.
10. The method for preparing a carbon dioxide-based resin coating according to claim 9, characterized in that: The extrusion temperature of the extrusion granulation in step 1) is 110°C to 120°C.
Citation Information
Patent Citations
Explosion-proof membrane
CN104118181A
CO2-based biodegradable copolymer composition as well as preparation method and application thereof
CN116285284A
Cited By
Spot-spraying varnish for vehicle and spraying repair process of spot-spraying varnish
CN120173466A